Association of Economic Impact, Social Impact, and Information Perception with Anxiety During the Coronavirus Disease Pandemic Among 4th year Students of Huacheiw Chalermprakiet University - Ngamkham, Nilawan; Sriraksa, Kanyaporn; Hinsoognern, Raksa; Supap, Wanida (Journal of Health Sciences and Wellness, 2022)
This cross-sectional descriptive research aims to study the anxiety level about the COVID-19 epidemic situation among senior students at Huachiew Chalermprakiet University and to examine the association of economic impact, social impact, and information perception with anxiety during the Coronavirus Disease Pandemic among 4th year students. The samples were senior students from Huachiew Chalermprakiet University. The sample group consisted of 261 senior students selected by a stratified random sampling technique. The content validity of questionnaires was proven by three experts. The Item-Objective Congruence Index (IOC) of all questions was 0.67–1.00. The Cronbach's alpha reliability test of the anxiety during the coronavirus disease pandemic, for economic impact, social impact, and information perception were 0.908, 0.908, 0.901, and 0.943, respectively. The findings of the study showed that anxiety during the coronavirus disease pandemic was at a high level, and that the variable having the biggest association with anxiety is Economic impact, followed by information perception, and social impact (b= 0.377, p<0.001; b= 0.347, p<0.001; b= 0.175, p<0.001, respectively). All the variables in the model could explain the anxiety level at 58.5% (R2=0.585). The findings of this study assist Huachiew Chalermprakiet University's administration in developing plans for income project activities, news tracking, and infection prevention in order to reduce anxiety during the Coronavirus Disease pandemic and emphasize economic impact, information exposure, and social impact, respectively.